IMPLEMENTATION OF THE NATIONAL MENTAL REVOLUTION MOVEMENT IN SUB-DISTRICT CARITA, PANDEGLANG REGENCY, BANTEN PROVINCE - Ajat Sudrajat; Ojat Darojat; Sofjan Aripin; Syaeful Mikdar; Heriyanto Heriyanto; Faizal Maulana; Ahmad Septianto (Universitas Lambung Mangkurat, 2021)
There is still a lack of knowledge on the society in Carita District, Pandeglang Regency, Banten Province about the importance of character values. It happens because that is a remote area so that they rarely get direction and guidance, especially related to the value of the character, the solution is the need for a workshop about Implementation of the National Movement of the Revolutionary Mental in Sub-district Carita, Pandeglang Regency, Banten Province. The GNRM workshop is a movement to change the way of thinking of society or youth, change the way of work that has been done so far to be more advanced, change the way of life, as well as attitudes and behavior of society which will further improve aspects of integrity, high ethical aspects and the spirit of mutual cooperation based on Pancasila and the 1945 Constitution. This workshop is divided into two themes, namely: a)